HDPS Cotton - Challenges and Opportunities in India - Ranapanga, Gouthami; Ramanjaneyulu, A. V.; Nagabhushanam, U.; Ramprasad, B.; Kamalakar, J.; Yakadri, M. (Chronicle of Bioresource Management, 2023)
This article provides a concise overview of the high density planting system employed in cotton farming. The adoption of high density planting system in cotton cultivation has led to increased yields vis-a-vis traditional planting methods. While the benefits of embracing high density planting system are evident, there are several challenges that farmers encounter throughout the cultivation process, spanning from sowing to harvesting. However, through the selection of appropriate cotton cultivars, the implementation of tailored cultivation techniques and the incorporation of mechanization in high density planting system of cotton farming, these challenges can be effectively addressed.